Negative Stereotypes of Ethnic Outgroups: A Longitudinal Examination Among Palestinian, Israeli Jewish, and Israeli Arab Youth. (24th October 2014) - Niwa, Erika Y.; Boxer, Paul; Dubow, Eric F.; Huesmann, L. Rowell; Landau, Simha; Shikaki, Khalil; Dvir Gvirsman, Shira
Abstract : Ethno‐political conflict impacts thousands of youth globally and has been associated with a number of negative psychological outcomes. Extant literature has mostly addressed the adverse emotional and behavioral outcomes of exposure while failing to examine change over time in social cognitive factors in contexts of ethno‐political conflict. Using cohort sequential longitudinal data, this study examines ethnic variation in the development of negative stereotypes about ethnic outgroups among Palestinian ( n = 600), Israeli Jewish ( n = 451), and Israeli Arab ( n = 450) youth over 3 years. Age and exposure to ethno‐political violence were included as covariates for these trajectories. Findings indicate important ethnic differences in trajectories of negative stereotypes about ethnic outgroups, as well as variation in how such trajectories are shaped by prolonged ethno‐political conflict.